Retratos dialógicos da clínica: um olhar discursivo sobre relatórios de atendimento psicopedagógico - Silva, Adriana Pucci Penteado de Faria e (2010)
In this thesis we discuss the discursive complexity of session reports written by Psychopedagogy students under supervised training and demonstrate the conflicts inherent in the work of a pre-service psychopedagogue, which involves the interaction between discursive partners: patients, student/psychopedagogue, and teacher/supervisor. With this aim, we searched for guidelines on Psychopedagogy regulations in Brazil, a field comprising professionals from various backgrounds and constituting the sphere of circulation of the reports. We then reflect on the procedures involved in the activity of writing at the clinical session, articulating scarce prescription on the theme with what can be inferred from a few published cases. Finally, we carry out an analysis of the session reports produced in the academic sphere. Considering that Psychopedagogy approaches the subject in its historical, social, desiring and relational dimension, we understand this subject as one of the voices present in the reports, being introduced in the writings of the student/psychopedagogue, the enunciator who leaves in those documents the marks of their emotional volitive center, around which the writing is organized. The apparent discursive tensions constituting the reports point to the appropriateness of Bakhtin-based dialogical theory as theoretical grounding for the identification of the forms of presence of different discursive voices and their architectonical forms upon which the theme of the utterance is constituted. The analytical corpus has been composed of: a) excerpts from reports corresponding to a clinical case conducted by pre-service students in the advanced diploma in Psychopedagogy at COGEAE/PUC-SP between March 2004 and February 2005; and b) excerpts from reports corresponding to two cases conducted in the second semester of 2007 by students in the Psychopedagogical Diagnosis class of the same program. The reports, being unique and unrepeatable concrete utterances, have their theme established from the discursive position of their author/enunciator. Thus, we take as premises to our research that: a) the connection between patient and knowledge is studied on the basis of the model of their first binding relationships; and b) the investigation of the relation between patient and the figures that take on the paternal and maternal roles results in the presence of the parental discourse in the sessions. From those premises, we propose the following hypothesis: if the dialogical analysis of the reports written by pre-service students on the basis of the psychopedagogical clinical activity reveals the discursive tensions between the voices present in such documents, then the perception of those tensions may contribute to the clinical study of the cases and to a reflection on the pre-service student/psychopedagogue s activity. The analyses show that the report brings a description of the clinic and makes apparent the reading which its author makes of the event, pointing to various angles from which the patient s discourse and those cited by them are interrelated. Besides, the dialogical reading of the reports shows that the instabilities concerning the legitimacy of the field mark the constitution of those utterances. Therefore, we hope this study will contribute to: 1) the understanding of the discursive nature of the reports and their role in the psychopedagogue s work; 2) the comprehension of the supervised cases, showing the pertinence of the Applied Linguistics/Psychopedagogy interface; and 3) a reflection on the establishment of Psychopedagogy as a clinical activity